An exploration of reciprocity among teacher and students in female pre-elite ballet: a shared reality theory perspective - Solstad, B. E.; Haraldsen, H. M.; Fredriksen, D.; Gustafsson, H.; Nordin-Bates, S.; Knight, C. J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction The teacher-student relationship is acknowledged as the heart of performance coaching, and a good quality relationship is deemed essential to enhance well-being and performance development. To establish such a quality relationship, a shared reality of mutual understandings, interests, and goals, as well as established trust and good communication appear vital. Despite the importance of this relationship, within the context of dance, it appears that there is an inconsistency between the ideal and actual in dance teaching, where teachers seem to overestimate the quality of their own teaching behaviors compared to their students` perceptions of the same teaching behaviors. However, there is a lack of theoretical understanding as to how and why such differences in perceptions arise and develop. Therefore, developing a more in-depth understanding of the establishing and quality of shared realities in asymmetric relationships, such as those between teachers and students in the performing arts, is particularly warranted.